Location and source characteristics of the 2016 January 6 North Korean nuclear test constrained by InSAR. Issue 2 (13th February 2017) - Wei, Meng
Summary: The interferometric synthetic aperture radar (InSAR) data from the Japan Aerospace Exploration Agency ALOS-2 satellite show possible deformation associated with the 2016 January 6 North Korean nuclear test whereas the European Space Agency Sentinel-1A data are decorrelated. This is the first time that deformation related to a nuclear test has been measured since 1992. Here, I present two interpretations of the observed deformation: First, the deformation can be explained by a triggered landslide on the western slope of Mt Mantap, with a displacement of up to 10 cm across a patch of 1 km 2 . Second, the observation may be from uplift created by the nuclear explosion. In the second interpretation, the location, depth and cavity size can be estimated from a topography-corrected homogenous half-space model (Mogi). The preferred location of the 2016 January 6 event is 41.2993°N 129.0715°E, with an uncertainty of 100 m. The estimated depth is 420–700 m and the cavity radius is 23–27 m. Based on empirical data and the assumption of granite as the host rock, the yield is estimated to be 11.6–24.4 kilotons of TNT, which is consistent with previous results based on seismic data. With these two interpretations, I demonstrate that InSAR data provide an independent tool to locate and estimate source characteristics of nuclear tests in North Korea. The ambiguity of interpretation is mainly due to the limited InSAR data acquisition. Future frequent data collection by current and upcoming InSAR satellites will allow full use of InSAR for nuclear monitoring and characterization in North Korea and around the world.